Femtosecond Laser and Mechanical Dissection for ICRS and MyoRing Implantation: A Meta-Analysis. Issue 4 (23rd April 2022) - Struckmeier, Ann-Kristin; Hamon, Loïc; Flockerzi, Elias; Munteanu, Cristian; Seitz, Berthold; Daas, Loay
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The aims of this meta-analysis were to evaluate the results of intracorneal ring segments (ICRSs) and MyoRing in the management of corneal ectasia and to compare the clinical outcomes and complication rates between mechanical and femtosecond (FS) laser-assisted surgery. Methods: An online electronic search was performed for pre–post studies published until April 2020. Uncorrected distance visual acuity, corrected distance visual acuity, sphere, cylinder, spherical equivalent, steep, flat, and mean keratometry values were considered as outcomes. Weighted mean difference with 95% confidence interval was used as a pooled estimation of intervention efficacy. Results: Of 1484 potentially related studies, 115 studies were finally included in the meta-analysis. Findings of this meta-analysis demonstrated considerable improvement in visual, refractive, and keratometric outcomes in all ICRS models and MyoRing. Intrastromal tunnel creation with both methods yielded similar results. Complication rates were without exception higher when mechanical dissection was used. Conclusions: ICRS and MyoRing are appropriate treatment options for patients with corneal ectasia. Both techniques for tunnel creation are efficacious in achieving good visual, keratometric, and refractive results. Mechanical intrastromal tunnel creation is associated with much higher complication rates when compared with FS laser-assisted technique.